VEGETATIVE COMPATIBILITY GROUPS OF FUSARIUM OXYSPORUM, THE CAUSAL ORGANISM OF VASCULAR WILT ON ROSELLE IN MALAYSIA - K.H Ooi; B. SALLEH (SEAMEO BIOTROP, 1999)
Forty strains of Fusarium oxysporvm isolated from roselle (Hibiscus sabdariffa var. sabdariffa) showing vascular wilt symptoms in three states (Terengganu, Penang and Ipoh) in the northern Malaysian Peninsula were used to investigate the vegetative compatibility. Nitrate-nonutilizing (nil) mutants were recovered from all the strains tested and subsequently used to study vegetative compatibility groups (VCG) within the population by nit mutants pairings on minimal medium. Thirteen VCGs were found and none were vegetatively compatible with those of other formae speciales (f. spp.) such as asparagi and cubense, and non-pathogenic strains from paddy and oil palm. The results indicate that there is substantial genetic diversity in F. oxysporum that causes vascular wilt disease on roselle as reflected by multiple VCGs, but the distribution of strains into the VCGs is not even as there are 26 representatives in VCG-1001M, two in VCG-1003M and VCG-1013M and only one in the other VCGs. This study may provide new insight into the establishment of a new forma specialis off. oxysporum. Key words: Vegetative Compatibility Groups/M/ mutants/fitsarium oxysporwrn/Roselle/Vascular wilt/ Malaysia.